Basic Research Skills Training - Pratama, Aditya; Siti Fatimah Zahra (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
The workload of a lecturer is not only about teaching ability, research but also demands for community service, the workload is stated in the law known as the Tri Darma of Higher Education. In terms of teaching, good teaching skills in a lecturer are of course an absolute must for a lecturer. Likewise with the obligations in research (making scientific papers), a lecturer must be able to make research that can be published both at the national and international levels. However, the scientific works produced by lecturers in Indonesia and published internationally are still relatively few. This is partly because lecturers are not given enough encouragement and support to be motivated in making scientific works. There should be various trainings and journal access facilities as a form of strategy to increase lecturer competence in writing scientific articles. Therefore, the PKM team took the initiative to carry out community service related to training on scientific work preparation skills to assist lecturers in improving the quality and quantity of their scientific publications. This activity consists of 3 stages, namely the preparation stage, the training implementation stage, and the activity evaluation stage. The existence of this PKM seems to be able to improve the participants’ abilities in making good scientific works